Efficacy and safety of low dose alteplase for intravenous thrombolysis in Asian stroke patients: a meta-analysis. Issue 1 (December 2017) - Tan, Ge; Wang, Haijiao; Chen, Sihan; Chen, Deng; Zhu, Lina; Xu, Da; Zhang, Yu; Liu, Ling
Abstract Whether low dose alteplase is comparable to standard dose in efficacy and safety for intravenous thrombolysis (IVT) in Asian stroke patients remains unverified. PubMed, EMBASE, and Cochrane Library Database from the beginning to June 30, 2017 were searched. IVT efficacy was measured by favorable outcome (modified Rankin Scale scores of 0–1) at 3 months, and safety measured by mortality within 3 months and symptomatic intracerebral hemorrhage (SICH). Pooled estimates were conducted using fixed- or random-effects model depending on heterogeneity. For SICH, studies were pooled separately according to different definitions. Twelve studies involving 7, 905 participants were included. No association was found between alteplase dose and favorable outcome (OR = 0.94, 95% CI 0.78–1.14, P = 0.5; heterogeneity:P hetero = 0.01, I2 = 57.3%) and mortality (OR = 0.87, 95% CI 0.74–1.02, P = 0.08;P hetero = 0.83, I2 = 0) using random- and fixed-effects models, respectively. Low dose alteplase was associated with lower SICH as defined by the National Institute of Neurological Disorders and Stroke study (OR = 0.79, 95% CI 0.64–0.99, P = 0.04;P hetero = 0.57, I2 = 0) using fixed-effects model. Subgroup and sensitivity analysis could change the results significantly. Current limited evidence was insufficient to support the speculation that low dose alteplase was comparable to standard dose in thrombolytic efficacy and safety in Asian stroke patients.